Work Autonomy on Elementary School Teachers’ Innovative Work Behavior: Mediation of Intrinsic Motivation and Organizational Commitment - Yoseph Doni Prasetyo; Lukas Purwoto (Journal of Innovation in Educational and Cultural Research, 2024)
Education plays an important role in forming a quality generation that contributes positively. This research pays attention to work autonomy and innovative work behavior in education. The research aims to understand the role of intrinsic motivation and organizational commitment in the relationship between work autonomy and innovative work behavior in school teachers. This research took a sample of 183 elementary school teachers from various school branches in various cities, namely Tangerang, Central Jakarta, West Jakarta, South Jakarta, North Jakarta, and East Jakarta. Data was collected through distributing questionnaires and then analyzed using the PLS-SEM quantitative analysis strategy. The research results show that teachers need work autonomy to increase innovative work behavior, both directly and indirectly, through intrinsic motivation. As evidenced through research analysis, this study contributes to the existing literature by showing a mechanism that can occur in the influence of work autonomy on innovative work behavior. Even more, these findings have implications for effective school policy and management.